PEMANFAATAN PERPUSTAKAAN DAN INTERNET UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR - Puji Astutik, (Pendidikan Ekonomi, 2011)
The study is intended to find out the influence of libraries and internet access on the students achievement with motivation as the intervening variable.  This study is explanatory research with quantitative approach.  Questionnaires and documents were used as the research instruments. The subjects of the study were the students of Accounting education study program at the State University of Surabaya. Path analysis was used as the data analysis technique. The result of the study reveals the existence of libraries and internet access influences the students learning achievement with motivation as the intervening variable.